PENGEMBANGAN PRODUK SUSU KEDELAI BUBUK MENGGUNAKAN INTEGRASI METODE VALUE ENGINEERING DENGAN FUZZY LOGIC - , Andita Sayekti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Criteria of consumer perceptions in design and development of products is an important factor for the success of the resulting products. Soybean (Glycine max (L.) Merill) is one source of vegetable protein and non cholesterol. Soy milk powder products is one of alternative processed soybean raw material which has a high economic value that can spur an increase in raw material usage at the level of postharvest soybean farmers. Consumer needâs factor for determining priority level of important attribute often overlooked uncertainty element and can not be strictly (crisp) set. Development of soy milk powder products using Value Engineering with Fuzzy Logic integration at the information stage (stages of development priorities) and the determination of the stage (stage zero-one method). Integration of Fuzzy Logic method used to fix the limit values represented by composing the membership functions. By this research, obtained attributes that overlooked by the consumers such as color, aroma, taste, price, packaging, nutritional content, and viscosity. Based on the stage of creativity found 5 product concept development of soy milk powder, which is: A product concept (original flavor)